Nonfunctional parathyroid cyst: case report - Nardi, Carlos Eduardo Molinari (2009)
CONTEXT: Parathyroid cysts are rare clinical and pathological entities, with less than 300 cases reported. The inferior parathyroid glands are most commonly involved, with left-side predominance. Parathyroid cysts may be functional or nonfunctional, depending on their association with hypercalcemia. CASE REPORT: A 25-year-old man presented a palpable asymptomatic left-side neck mass. Ultrasound revealed a cystic structure contiguous with the left thyroid lobe. Serum ionic calcium was normal. The patient underwent left thyroid lobectomy plus isthmectomy with excision of the cyst. The histological findings revealed a parathyroid cyst. Parathyroid cysts typically present as asymptomatic neck masses, and surgical excision appears to be the treatment of choice.